The eye of the monkey - Jones, Gareth P. (Jones, Gareth P. Ninja meerkats, 2013)
"An Indian emerald with mystical powers has been stolen from under the noses of the monkeys who guard it. The meerkats team up with kung fu supremo the Delhi Llama to investigate."--Page [4] of cover.